Investigating Between Patient Safety Culture, Organizational Climate, and A Positive Workplace on Reporting of Patient Safety Incidents in Hospital - Dian Widya Christiany Jacobus; Yuliani Setyaningsih; Septo Pawelas Arso (Universitas Muhammadiyah Yogyakarta, 2024)
Many patient safety incidents (PSIs) begin the hospital's safety system establishment, which is oriented toward patient safety. The importance of PSI reporting is of particular concern to WHO. Therefore, comprehensive guidance exists on designing, implementing, and applying good PSI reporting. This research is a non-experimental design using SEM analysis techniques, and it is processed using the SMARTPLSv3 application. This study aims to determine the effect of patient safety culture (X1), organizational climate (X2), and a positive environment (X3) on motivation to report PSI (Y1). The research sample was the X Semarang Hospital staff, with 200 respondents. The results showed that the Patient Safety Rate at X Semarang Hospital was in a suitable category of 54%, even though the number of PSI reported was in the low category. The SEM analysis result indicated that the construct of the X1 and X2 variables after modification was valid and reliable. Moreover, there was a positive and significant effect of X1 and X2 on Y1 with an effect size of 0.042 (small) and 0.490 (large). However, X2 did not have a significant influence on Y1. The hierarchy culture implemented in X Hospital didn't affect motivation for the reporting of patient safety incidents (PSI). It even tends to have an indirect negative influence through a supportive environment variable.